2017
DOI: 10.1016/j.ecolind.2016.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the distribution of infralittoral Cystoseira populations on pristine coasts of four Tyrrhenian islands: Proposed adjustment to the CARLIT index

Abstract: The influence of geomorphological features on the distribution of Cystoseira populations along the coasts of four pristine islands in the Tyrrhenian Sea (Italy, central Mediterranean) was studied by means of a model-based statistical analysis. The most relevant trait that determined the presence of these populations was found to be the coastline slope at the level of the infralittoral fringe. Our findings indicate that slopes above 60 • reduce the likelihood of Cystoseira communities. The effects of the coastl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Despite the absence of the species with the highest sensitivity level (C. amentacea), ES values belonging to the "good" class have been recorded also in this area within some water bodies. This outocome matched with the findings of a recent study according to which, in absence of anthropogenic pressures, the distribution of C. amentacea of the infralittoral fringe can be induced by the morphology of the coast, mainly related to the coastline slope [16]. Urbanization, including articialization of the coastline and sewage, are known to affect the very shallow communities, together with industrial impacts, as observed in many Mediterranean areas [5,6,19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the absence of the species with the highest sensitivity level (C. amentacea), ES values belonging to the "good" class have been recorded also in this area within some water bodies. This outocome matched with the findings of a recent study according to which, in absence of anthropogenic pressures, the distribution of C. amentacea of the infralittoral fringe can be induced by the morphology of the coast, mainly related to the coastline slope [16]. Urbanization, including articialization of the coastline and sewage, are known to affect the very shallow communities, together with industrial impacts, as observed in many Mediterranean areas [5,6,19].…”
Section: Discussionsupporting
confidence: 89%
“…Urbanization, including articialization of the coastline and sewage, are known to affect the very shallow communities, together with industrial impacts, as observed in many Mediterranean areas [5,6,19]. Agricultural discharges and illegal domestic/urban outfalls are most likely responsible of a moderate to poor ES in some sectors of the Sicilian coastline (WB 5,15,16,17,22,23,24). However, only two water bodies (WB 16 and 24) did not yet fulfill the WFD requirements being classified as "moderate".…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we reported the presence of brown macroalgae (especially Cystoseira spp., Figure 8b-d). This species is very important along rocky coasts because well-developed Cystoseira belt communities indicate good water quality [67] and, in general, arborescent macro-algae forests covering temperate rocky reefs are a known habitat for juvenile fish [68]. On the other hand, the southern part of the P. oceanica meadow presented an impacted area (represented by dead "matte", Figure 8e-g) near to the port, probably due to the works for the expansion of the breakwater.…”
Section: Nursery Area Of Juvenile Fishmentioning
confidence: 99%
“…The selection of a proper reference site is fundamental for the CARLIT Index calculation [2]. This index is widely used in the EU Mediterranean countries: Spain (Catalan coast [1], Alboran Sea [3]); France (Southern coast and Corsica [4]); Italy ([5], Ligurian Sea [2, 6], Gulf of Naples [7], Northwestern Adriatic Sea [8], Sardinia [9], Tyrrhenian islands [10]); Croatia (Northeastern Adriatic Sea [11], Malta [12]) and in three non-EU countries: Albania [13], Tunisia [14] and Lebanon [15].…”
Section: Introductionmentioning
confidence: 99%